2020
DOI: 10.1136/bmjopen-2019-036465
|View full text |Cite
|
Sign up to set email alerts
|

Rates, causes, place and predictors of mortality in adults with intellectual disabilities with and without Down syndrome: cohort study with record linkage

Abstract: ObjectivesTo investigate mortality in adults with intellectual disabilities: rates, causes, place, demographic and clinical predictors.DesignCohort study with record linkage to death data.SettingGeneral community.Participants961/1023 (94%) adults (16–83 years; mean=44.1 years; 54.6% male) with intellectual disabilities, clinically examined in 2001–2004; subsequently record-linked to their National Health Service number, allowing linkage to death certificate data, 2018.Outcome measuresStandardised mortality rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 25 publications
(47 reference statements)
6
37
1
1
Order By: Relevance
“…Three studies, however, did not report mortality by the severity of ID ( 44 , 46 , 50 ). Mortality in ID was significantly increased by genetic disorders (Down syndrome and Fragile X), maternal alcohol use, low-birth weight and postnatal injury, and the presence and number of comorbid neurological conditions such as epilepsy and cerebral palsy ( 43 , 45 , 48 , 51 ) ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies, however, did not report mortality by the severity of ID ( 44 , 46 , 50 ). Mortality in ID was significantly increased by genetic disorders (Down syndrome and Fragile X), maternal alcohol use, low-birth weight and postnatal injury, and the presence and number of comorbid neurological conditions such as epilepsy and cerebral palsy ( 43 , 45 , 48 , 51 ) ( Table 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Respiratory infections (34%), accidents (18%), and epilepsy (10.7%) were the most common causes of death in ID in one study from Western Australia ( 43 ); while, the leading causes of death in a Swedish study were congenital malformations (SMR 46.3 [32.9–65.0]), neurological diseases (SMR 9.7 [5.5–17.0]), mental disorders (SMR 4.0 [1.9–8.4]), and respiratory diseases (SMR 3.3 [2.0–5.5]) ( 45 ). Diseases of the respiratory system (21.8%), the circulatory system (19.1%) and the nervous system (13.0%) were the most common causes of death in the Scottish study ( 51 ). Another Scottish study ( 50 ) identified diseases of the nervous system (33%), congenital malformations, deformations and chromosomal anomalies (22%), and nutritional, metabolic and endocrinal diseases (8%) as the most frequent causes of death.…”
Section: Resultsmentioning
confidence: 99%
“…2 Poorer health outcomes compared with the general population have been consistently reported for people with ID, 3 with an increased incidence of comorbidities including dysphagia and respiratory diseases, with respiratory disease identified as a leading cause of death. 4 These health comorbidities are associated with poor outcomes following infections and other acute conditions, 5 6 which may be exacerbated by barriers in accessing health and social care, associated with concerns about ongoing discrimination and bias. 7 To date there have been over 64 million cases of COVID-19 reported worldwide and 1.4 million deaths.…”
Section: Introductionmentioning
confidence: 99%
“…(1) The WHO defines intellectual disabilities as impairments in adaptive, social, and intellectual functioning (IQ<70), requiring daily support, with the onset in the developmental phase (<18 years). (2) People with intellectual disabilities account for <1% of the global population,(3, 4) and about 0.5% of adults, (4) and they experience substantial health inequalities, including multimorbidity,(5) and premature and avoidable mortality,(6, 7) often from respiratory conditions. (8, 9) They are also more likely to live in congregate settings or be in receipt of social care (10); recent studies have reported high rates of COVID-19 mortality within multi-occupancy residences.…”
Section: Introductionmentioning
confidence: 99%